2008
DOI: 10.1002/mrc.2307
|View full text |Cite
|
Sign up to set email alerts
|

Structural elucidation of propargylated products of 3‐substituted‐1,2,4‐triazole‐5‐thiols by NMR techniques

Abstract: Propargylation of 3-substituted-1,2,4-triazole-5-thiols, which predominantly exist as their thione tautomers, was carried out with the view to synthesize different heterocycles and study their biological activity. Three different products namely, a mono S-propargyl and two S,N-dipropargyl regioisomers, arising from N1/N2 substitution, were isolated and characterized. Unambiguous structural elucidation of the regioisomers of S,N-dipropargyl derivatives was achieved by means of (13)C-(1)H HMBC technique. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…The propargylation of thiones of interest, although in principle can give rise to three di-substituted products 3a, 3b, and 3c (Scheme 1), gave only two di-substituted products 5-substituted-1-(prop-2-ynyl)-3-(prop-2-ynylthio)-1H-1,2,4-triazole (3a) and 3-substituted-1-(prop-2-ynyl)-5-(prop-2-ynylthio)-1H-1,2,4-triazole (3b). [14] The results of the theoretical calculation presented in Table 5 showed that 3c is the least stable regioisomer in R 1 = H case. The energy difference between 3a and 3b for this case is very small (~0.5 kcal/mol) in favor of 3a, whereas it is large between 3b and 3c (10.60 kcal/mol).…”
Section: Dipropargyl Derivativesmentioning
confidence: 95%
See 4 more Smart Citations
“…The propargylation of thiones of interest, although in principle can give rise to three di-substituted products 3a, 3b, and 3c (Scheme 1), gave only two di-substituted products 5-substituted-1-(prop-2-ynyl)-3-(prop-2-ynylthio)-1H-1,2,4-triazole (3a) and 3-substituted-1-(prop-2-ynyl)-5-(prop-2-ynylthio)-1H-1,2,4-triazole (3b). [14] The results of the theoretical calculation presented in Table 5 showed that 3c is the least stable regioisomer in R 1 = H case. The energy difference between 3a and 3b for this case is very small (~0.5 kcal/mol) in favor of 3a, whereas it is large between 3b and 3c (10.60 kcal/mol).…”
Section: Dipropargyl Derivativesmentioning
confidence: 95%
“…Information about the presence of tautomer 2a could be established from 1 H- 13 C HMBC spectra where the NH proton showed correlations only to the carbons in the heterocyclic ring and not to the carbon on the substituent R 1 . [14] For the mono-substituted cases, chemical shifts for some of the nitrogen atoms (e.g. N4 atom) in the heterocyclic ring could not be obtained because of the absence of cross peak in HSQC/HMBC spectra under the measurement conditions.…”
Section: Mono-propargylated Derivativesmentioning
confidence: 98%
See 3 more Smart Citations